Minimally invasive atrioventricular valve surgery – current status and future perspectives - Van der Merwe, J.; Casselman, F.; Van Praet, F. (SA Heart Journal, 2019)
We are currently witnessing rapid evolution in minimally invasive and catheter-based atrioventricular valve interventions as acceptable alternatives to classic sternotomy access (CSA). Collectively, minimally invasive atrioventricular valve surgery (MIAS) is associated with significant learning curves and its routine application is met with varying degrees of enthusiasm in view of strict quality control, clinical governance and outcome reporting. Whether the reported potential benefits and comparable efficacy across a range of long-term outcome measures reported by experienced MIAS centres can be translated into general international surgical practice, are not well defined. This paper describes the historic evolution of MIAS, the contemporary clinical outcomes of MIAS compared with CSA, and the application of MIAS in “real-life” general practice.